Teori Bank Syariah - Hamdi Agustin (LPPM ISNJ Bengkalis, 2021)
The purpose of this research is to re-conceptualize the theory of Islamic banking according to the Al-Quran and Hadith. This research needs to be carried out considering that the operational activities of Islamic banks, especially in Indonesia, have been heavily criticized by academic researchers because there have been several deviations from Islamic banking activities that are not in accordance with the provisions of Islamic law. The method used in this research is the method of documentation and reviewing secondary data in the form of theories regarding Islamic banking. The analysis technique used is descriptive. Where the development of Islamic banking literature will be explained in a complete and structured manner so that it will produce an in-depth explanation. The results showed that the theory of Islamic banking is shaped like a building where the foundation of Islamic banking is faith-based on the Al-Quran and Hadith and carries out the characteristics of the Prophet Sallallaahu ‘Alaihi Wasallam. After the foundation is in place, it can run the rules of Islamic banking based on sharia which consists of prohibition of all usury practices, prohibition of financing maysir and gharar businesses, financing of real assets, sharing of profits and risk of loss. If sharia has been implemented in sharia banking, a pure sharia bank will be realized so that it will get the blessing of Allah Ta'ala.